The Middle Acheulian Occupation Site at Latamne, Northern Syria - Clark, J. Desmond
ersch. 1967; Introduction – Stratigraphy – Artifacts in the Red, Calcic Soil – The Excavation of the Acheulian Occupation Area – Terminology – Raw Material – Composition of the Archaeological Horizon – Description of Artifact Classes – Bone from the Occupation Area – Comparisons; ١٣-٢٦ arabisch.